Understanding collaborative problem-solving on the move: A design science research journey - Rosemary Francisco; Amarolinda da Costa Zanela Klein (BAR: Brazilian Administration Review, 2020)
The emergence of globally distributed teams and the evolution of mobile technologies have increased the number of mobile knowledge workers (MKW). MKW are professionals who frequently work on the move, far from a fixed workplace, performing knowledge-intensive activities. MKW often work alone, which leads them to face constant challenges in their work practices and difficulties to get timely knowledge to solve their problems alone. Still, little is known about how the collaborative problem-solving is carried out in the MKW’s context. To address this gap, we adopted the Design Science Research (DSR) as a research method, and we applied activity theory (AT) and expansive learning as theoretical foundations to understand the MKW’s context. We created an artifact — a method implemented via a mobile app — to support collaborative problem-solving processes on the move, which allowed us to understand better how these processes occur, contributing not only to problems resolutions but also to organizational learning.